A Basic Theory of Everything A Fundamental Theoretical Framework for Science and Philosophy - Søvik, Atle Ottesen (De Gruyter, 2022)
What are the basic building blocks of the world? This book presents a naturalistic theory saying that the universe and everything in it can be reduced to three fundamental entities: a field, a set of values that can be actualized at different places in the field, and an actualizer of the values. The theory is defended by using it to answer the main questions in metaphysics, such as: What is causality, existence, laws of nature, consciousness, thinking, free will, time, mathematical entities, ethical values, etc.? The theory is compared with the main alternatives and argued to solve problems better than the existing theories. Several new theories are suggested, such as how to understand mental causation, free will and the truth of ethics and mathematics.